Analisis Permasalahan Siswa Kelas 1 SDN Panggilingan 02 Dalam Melaksanakan Pembelajaran - Fitria Nur Auliah Kurniawati; Asep Rudi Nurjaman (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
One important factor that can affect human development is education in schools. School education is obtained by students through learning activities in schools in a systematic, regular and sustainable manner starting from Kindergarten (TK) to tertiary institutions. It is through elementary school education that humans can get a foundation/pillar that can help humans to acquire basic knowledge as a provision to continue their education to a higher level and be able to develop properly in society. This research uses descriptive qualitative research methods, data collection techniques, namely by literature review, observation, interviews, and documentation, as well as research instruments in the form of observation papers, interview guides, and other complementary documents such as books and scientific articles. This research method was used because the researcher considered that it was in accordance with the purpose of this study, which was to describe the conditions that occurred and obtain solutions to problems that occurred in early elementary school students, especially grade 1 students at SD Negeri Callingan 02. Through this research, researchers found several problems students in class such as 1) No motivation to learn, 2) Difficulty getting along, 3) Not remembering what has been learned, test schedules, and class schedules, etc. as well as several solutions that can inspire teachers and parents who have the same problem